A Framework for Assessing the Performance of Nonprofit Organizations. (September 2015) - Lee, Chongmyoung; Nowell, Branda
Performance measurement has gained increased importance in the nonprofit sector, and contemporary literature is populated with numerous performance measurement frameworks. In this article, we seek to accomplish two goals. First, we review contemporary models of nonprofit performance measurement to develop an integrated framework in order to identify directions for advancing the study of performance measurement. Our analysis of this literature illuminates seven focal perspectives on nonprofit performance, each associated with a different tradition in performance measurement. Second, we demonstrate the utility of this integrated framework for advancing theory and scholarship by leveraging these seven perspectives to develop testable propositions aimed at explaining variation across nonprofits in the adoption of different measurement approaches. By better understanding how performance measurement is conceptualized within sector, the field will be better positioned to both critique and expand upon normative approaches advanced in the literature as well as advance theory for predicting performance measurement decisions.